2019
DOI: 10.1002/pon.5295
|View full text |Cite
|
Sign up to set email alerts
|

When mental illness and cancer collide: An investigation of the predictors of outcomes for cancer patients with a history of mental health problems

Abstract: Objective People with a serious mental health condition are no more likely to receive a diagnosis of cancer than the general population but fare more poorly in terms of outcomes. The current study investigated whether a background of mental health problems (measured by contact with mental health services and psychotropic medication) predicted treatment outcomes over and above demographic and medical confounds for cancer patients at Counties Manukau Health. Methods The sample consisted of 1652 patients diagnose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 7 publications
2
5
0
4
Order By: Relevance
“…We found having a history of mental disorder, excessive drinking, and having higher levels of fatigue and pain were the predominant risk factors for mental health problems in cancer patients. Consistent with previous research 14 , we found that more severe mental health problems in cancer patients were associated with somatic comorbidities, especially in terms of pain and fatigue. During the COVID-19 pandemic, there were more than one-third of patients who reported having some barriers to continue their cancer treatment due to inconveniences caused by COVID-19.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We found having a history of mental disorder, excessive drinking, and having higher levels of fatigue and pain were the predominant risk factors for mental health problems in cancer patients. Consistent with previous research 14 , we found that more severe mental health problems in cancer patients were associated with somatic comorbidities, especially in terms of pain and fatigue. During the COVID-19 pandemic, there were more than one-third of patients who reported having some barriers to continue their cancer treatment due to inconveniences caused by COVID-19.…”
Section: Discussionsupporting
confidence: 92%
“…Left untreated mental health problems in cancer patients can led to destructive consequences including decreased treatment adherence, decreased survival rate, increased healthcare cost, and poor quality of life [10][11][12][13] . Research has shown that cancer patients with severe mental health problems are more likely to be hospitalized and die in 12 months after their cancer diagnosis when compared to patients without or with less severe mental health problems 14 .…”
Section: Introductionmentioning
confidence: 99%
“…This may be interpreted by the fact that new pain meant deterioration of the health status and thus meant the need for hospitalization or doctor follow‐up and clinic visit, and during the pandemic this was not always accessible and it created a burden to the patient due to the fear of getting infected if they had to visit the medical clinics or to be hospitalized. 47 On the contrary, in a study carried out by Letaief‐Ksontini et al. they found no significant relationship between depression and suffering from body pain.…”
Section: Discussionmentioning
confidence: 91%
“…These finding suggest that during the pandemic, stressors like new body pain in patients diagnosed with cancer contribute to more depression than in patients who did not suffer new pain or often had new pain. This may be interpreted by the fact that new pain meant deterioration of the health status and thus meant the need for hospitalization or doctor follow‐up and clinic visit, and during the pandemic this was not always accessible and it created a burden to the patient due to the fear of getting infected if they had to visit the medical clinics or to be hospitalized 47 . On the contrary, in a study carried out by Letaief‐Ksontini et al.…”
Section: Discussionmentioning
confidence: 99%
“…A literatura aponta também que outras características estão relacionadas ao enfrentamento do paciente oncológico, como o sexo (feminino), idade (pacientes jovens), estado civil, menor escolaridade, tratamento cirúrgico ou quimioterápico prévio, tempo de diagnóstico, histórico de saúde mental vulnerável estiveram associados com maior prevalência de transtornos mentais, desenvolvimento ou persistência desses distúrbios (Hemmington et al, 2019;Blázquez & Cruzado, 2016;Pérez-Fortis et al, 2018). Almigbal et al (2019) encontraram também que o tipo de câncer dos pacientes foi significativamente associado ao nível de sofrimento físico, emocional e sintomas depressivos.…”
Section: Introductionunclassified